A Mussel‐Inspired Conductive, Self‐Adhesive, and Self‐Healable Tough Hydrogel as Cell Stimulators and Implantable Bioelectronics. Issue 2 (25th October 2016) - Han, Lu; Lu, Xiong; Wang, Menghao; Gan, Donglin; Deng, Weili; Wang, Kefeng; Fang, Liming; Liu, Kezhi; Chan, Chun Wai; Tang, Youhong; Weng, Lu‐Tao; Yuan, Huipin
Abstract : A graphene oxide conductive hydrogel is reported that simultaneously possesses high toughness, self‐healability, and self‐adhesiveness. Inspired by the adhesion behaviors of mussels, our conductive hydrogel shows self‐adhesiveness on various surfaces and soft tissues. The hydrogel can be used as self‐adhesive bioelectronics, such as electrical stimulators to regulate cell activity and implantable electrodes for recording in vivo signals.